Photopolymer resins for luminescent three‐dimensional printing. Issue 32 (2nd May 2017) - Wang, Fei; Chong, Yiting; Wang, FuKe; He, Chaobin
ABSTRACT: Liquid resins‐based three‐dimensional (3D) printing techniques such as stereolithography and digital light processing (DLP) show higher resolution and accuracy than other printing techniques, but their applications have been impeded by the limited materials selection and lack of functions. We here reported the preparation of luminescent resins for DLP‐based 3D printing. Homogeneous dispersion of the fluorescent dyes was achieved by small acrylate molecules screening, and the cure depth studies was used to optimize both resin composition and printing parameters setting. In addition, we showed that the optical analysis of absorption and emission spectra is an important tool to reduce the complex mutual‐interference of the light absorption of dye, photoinitiator and photo‐absorber in the printable resin. We also developed the mater batch technique to tune the emitting colors in the whole visible range, together with white emitting. By using the developed resins, different 3D structures with different emitting colors were successfully printed by DLP technique. These results will further widen the applications of the liquid resins‐based 3D printing techniques, and these luminescent resins show highly potential applications in education, lighting, UV converters, and so on. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44988. Abstract :